Ozonated saline intradermal injection: promising therapy for accelerated cutaneous wound healing in diabetic rats - Hesham, Ahmed; Abass, Marwa; Abdou, Haanin; Fahmy, Reham; Rashad, Maha M.; Abdallah, Abdelnaser A.; Mossallem, Wael; Rehan, Ibrahim F.; Elnagar, Asmaa; Zigo, František; Ondrašovičová, Silvia; Abouelnaga, Ahmed F.; et al. (Frontiers in Veterinary Science, 2023)
The use of ozonized water is gaining importance in medicine due to its effects on hyperglycemia and wound healing mechanisms. This experiment was conducted to assess the impacts of intradermal administration of ozonated water on acute skin wound healing in a diabetic rat model. Sixty-four adult male Wistar rats were randomly divided into two groups: an ozonated water group (O3W) and a control group (CG). Experimental diabetes was chemically induced in the rats by the intraperitoneal administration of 60 mg/kg streptozotocin. One week later, full-thickness skin surgical wounds (1 cm2) were created between the two shoulders of the rats under general anesthesia. The wounds were then daily irrigated with normal saline (CG) or intradermally injected with 1 ml of ozonated water at 10% O3W. Wound healing was evaluated through macroscopic analysis, measuring wound size, diameter, and percentage of contraction rate before wounding and at 3, 7, 9, 12, 14, 18-, 21-, 24-, and 28 days post-wounding. On days 7, 14, 21, and 28 after induction of the wounds, the body weights and blood glucose levels of rats (8 per group) were measured before the rats were euthanized. Moreover, the morphological structure of the tissue, vascular endothelial and transforming growth factor (VEGF and TGF) affinity and gene expression were examined. Results showed that the O3W group had significantly lower blood glucose levels and wound size and gained body weight. Additionally, epithelial vascularization, stromal edema, TGF, and VEGF gene expression significantly improved in the O3W group. Therefore, ozonated water has the potential to enhance and promote cutaneous wound healing in diabetic rats.